Melampaui Batas Fisik: Segregasi Sosial dalam Kontestasi Ruang Keagamaan Perkotaan: Beyond Physical Boundaries: Social Segregation in Contestation Urban Religious Space - Abdul Azisurrohman; Nur Rif’ah Hasaniy (IAIN Parepare, 2024)
Religious spatial segregation is an increasingly prominent phenomenon in Indonesia's urban landscape. This study analyzes how the spatial dimension of religion contributes to polarization and conflict between religious groups in urban societies. Using a qualitative descriptive approach and literature review method, this research explores the forms, impacts, and prevention efforts of religious spatial segregation through analysis of cases involving the dissolution of religious rituals and rejection of houses of worship construction. Based on the concept of Religion and Space by Lili Kong and Orlando Wood, this study argues that the spatial dimension of religion reinforces the boundaries of religious differences, transforming them from imaginary to clear and practical boundaries, thus giving rise to tensions between religious groups. Furthermore, social segregation is created not only due to the monopolization of space by religious identities but also because space is always associated with power and regulation. To address religious violence resulting from segregation, this study proposes a peacebuilding design with an integrative structural and socio-cultural approach. The research findings indicate that the concept of religious spatiality is ambiguous and paradoxical, where blurred categorizations of space trigger contestation of meaning between groups, potentially leading to conflict and violations of religious freedom. This study contributes to a more comprehensive understanding of the dynamics of religious conflict in urban contexts and highlights the importance of a spatial approach in conflict resolution and peacebuilding efforts.